A análise do discurso diante de estranhos espelhos: visualidade e (inter)discursividade na pintura - Mazzola, Renan Belmonte [UNESP]; Gregolin, Maria do Rosário Valencise [UNESP] (LAEL/PUC-SP (Programa de Estudos Pós-Graduados em Linguística Aplicada e Estudos da Linguagem da Pontifícia Universidade Católica de São Paulo), 2013)
This paper aims to understand the discursive dimension of some paintings through Michel Foucault'sdiscourse analysis approach. The image of the mirror in several canonical paintings was selected, intending to observe its discursive operation as an element of the visual artistic utterance. Basically, this text has three parts: firstly, it determines the place occupied by the aesthetic discourse in Michel Pêcheux's and Michel Foucault's works; secondly, it focuses on the analysis of three European paintings, namely The Maids of Honour by Velásquez, A Bar at the Folies-Bergère by Manet, and Dangerous Liaisons by Magritte; thirdly, it discusses the intersection between visuality and interdiscursivity based on a) the contributions of M. Foucault's works on aesthetic discourse and b) the image of the mirror found in those paintings.

Este artigo intenciona compreender a dimensão discursiva das pinturas por meio da análise do discurso ancorada em Michel Foucault. Recorta-se a figura do espelho em pinturas canônicas com vistas a observar seu funcionamento discursivo enquanto elemento do enunciado artístico visual. Apresenta três partes: a primeira, que determina o lugar ocupado pelo discurso estético nos trabalhos de Michel Pêcheux e de Michel Foucault; a segunda, que se concentra na análise de três pinturas europeias, a saber, As meninas, de Velásquez; Um bar em Folies-Bergère, de Manet; e As ligações perigosas, de Magritte; e a terceira parte, que discute a intersecção entre visualidade e interdiscursividade a partir (a) das reflexões de M. Foucault acerca do discurso estético e (b) da figura do espelho presente nessas pinturas.
Discourse analysis before strange mirrors: visuality and (inter)discursivity in painting
Keywords: Análise do discurso; Discurso estético; Michel Foucault; Discourse Analysis; Aesthetic Discourse; Michel Foucault